Association between mucosal barrier disruption by Pseudomonas aeruginosa exoproteins and asthma in patients with chronic rhinosinusitis. Issue 11 (9th June 2021) - Tuli, Jannatul Ferdoush; Ramezanpour, Mahnaz; Cooksley, Clare; Psaltis, Alkis James; Wormald, Peter‐John; Vreugde, Sarah
Abstract: Background: Chronic rhinosinusitis (CRS) is a common chronic respiratory condition, frequently associated with asthma and affecting the majority of cystic fibrosis (CF) patients. Pseudomonas aeruginosa infections and biofilms have been implicated in recalcitrant CRS. One of the mechanisms of action for bacteria in CRS and CF is mucosal barrier disruption by secreted products that contribute to the inflammation. However, the role of biofilm and planktonic forms of P . aeruginosa in this process is not known. The aim is to determine the effect of P . aeruginosa exoproteins isolated from CF and non‐CF CRS patients on the mucosal barrier. Methods: Exoproteins from 40 P . aeruginosa isolates were collected in planktonic and biofilm forms and applied to air‐liquid interface (ALI) cultures of primary human nasal epithelial cells (HNECs). Mucosal barrier integrity was evaluated by transepithelial electrical resistance (TEER), passage of FITC‐dextrans and immunofluorescence of tight junction proteins. Cytotoxicity assays were performed to measure cell viability, and IL‐6 ELISA was carried out to evaluate pro‐inflammatory effects. Results: Planktonic exoproteins from 20/40 (50%) clinical isolates had a significant detrimental effect on the barrier and significantly increased IL‐6 production. Barrier disruption was characterized by a reduced TEER, increased permeability of FITC‐dextrans and discontinuous immunolocalization of tight junction proteins and was significantly more prevalent in isolates harvested from patients with comorbid asthma ( P  < .05). Conclusion: Exoproteins from planktonic P . aeruginosa clinical isolates from asthmatic CRS patients have detrimental effects on the mucosal barrier and induce IL‐6 production potentially contributing to the mucosal inflammation in CRS patients. Abstract : Exoproteins from 40 Pseudomonas aeruginosa isolates of CRS patients were applied on ALI culture in planktonic and biofilm forms. Planktonic but not biofilm exoproteins show disruption of epithelial barrier (decreased TEER). The isolates that reduce TEER (high and intermediate effect) are associated with asthma in corresponding patients. Abbreviations: ALI, air‐liquid interface; CRS, chronic rhinosinusitis; HNEC, human nasal epithelial cells; IL‐6, interleukin ‐6; TEER, transepithelial electrical resistance; ZO‐1, zonula occludens 1